PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) PADA ATAP GEDUNG PARKIR BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI - Wira Dharma, Gede Agus; Giriantari, Dwi; Sukerayasa, I Wayan; Setiawan, I Nyoman; Ariastina, Wayan Gede; Satya Kumara, I Nyoman (Jurnal SPEKTRUM; Vol 11 No 2 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i02.p2, 2024)
Using sustainable energy as a source of electrical energy is a safe way to increase ecosystem energy. One of them is the utilization of photovoltaic directed energy by upgrading the PLTS on top of the structure as a mechanism for introducing photovoltaic modules. The study finalized the plan to install PLTS on the roof of the I Gusti Ngurah Rai Airport parking lot as a source of electrical energy to reduce PLN electricity bills. The I Gusti Ngurah Rai Airport Parking Roof Solar Power Plant uses a battery-free on gridsystem with 600 units of 555Wp monocrystalline solar-based modules and four 100kW inverter units. The solar power plant to be built on the car park of Terminal I Gusti Ngurah Rai will have a capacity of 333kWp and will produce 604.929kWh of energy annually. The required speculation cost is Rp 3.004.620.000 and payback period for 6 years.